Cracking the sales management code : the secrets to measuring and managing sales performance - Jordan, Jason, 1970-; Vazzana, Michelle (McGraw Hill-Ascent Audio, 2011)
Boost sales results by zeroing in on the metrics that matter most "Sales may be an art, but sales management is a science. Cracking the Sales Management Code reveals that science and gives practical steps to identify the metrics you must measure to manage toward success." -Arthur Dorfman, National Vice President, SAP "Cracking the Sales Management Code is a must-read for anyone who wants to bring his or her sales management team into the 21st century." -Mike Nathe, Senior Vice President, Essilor Laboratories of America "The authors correctly assert that the proliferation of management reporting has created a false sense of control for sales executives. Real control is derived from clear direction to the field-and this book tells how do to that in an easy-to-understand, actionable manner." -Michael R. Jenkins, Signature Client Vice President, AT&T Global Enterprise Solutions "There are things that can be managed in a sales force, and there are things that cannot. Too often sales management doesn't see the difference. This book is invaluable because it reveals the manageable activities that actually drive sales results." -John Davis, Vice President, St. Jude Medical "Cracking the Sales Management Code is one of the most important resources available on effective sales management. . . . It should be required reading for every sales leader." -Bob Kelly, Chairman, The Sales Management Association "A must-read for managers who want to have a greater impact on sales force performance." -James Lattin, Robert A. Magowan Professor of Marketing, Graduate School of Business, Stanford University "This book offers a solution to close the gap between sales processes and business results. It shows a new way to think critically about the strategies and tactics necessary to move a sales team from good to great!" -Anita Abjornson, Sales Management Effectiveness, Abbott Laboratories About the Book: There are literally thousands of books on selling, coaching, and leadership, but what about the particulars of managing a sales force? Where are the frameworks, metrics, and best practices to help you succeed? Based on extensive research into how world-class companies measure and manage their sales forces, Cracking the Sales Management Code is the first operating manual for sales management. In it you will discover: The five critical processes that drive sales performance How to choose the right processes for your own team The three levels of sales metrics you must collect Which metrics you can "manage" and which ones you can't How to prioritize conflicting sales objectives How to align seller activities with business results How to use CRM to improve the impact of coaching As Neil Rackham writes in the foreword: "There's an acute shortage of good books on the specifics of sales management. Cracking the Sales Management Code is about the practical specifics of sales management in the new era, and it fills a void." Cracking the Sales Management Code fills that void by providing foundational knowledge about how the sales force works. It reveals the gears and levers that actually control sales results. It adds clarity to things that you intuitively know and provides insight into things that you don't. It will change the way you manage your sellers from day to day, as well as the results you get from year to year.